Public awareness and perception of clinical trials in Montenegro - Mugoša Snežana S.; Kučević Berina I.; Rolevski Marta S.; Bukumirić Zoran M.; Bešović Željka M.; Drljević Milorad D. (Srpsko lekarsko drustvo, 2015)
Introduction: Clinical trials of medicines are crucial for obtaining relevant information on the efficacy and safety of medicines. Literature data showed that the general public is not sufficiently informed about the purpose and importance of clinical trials. The aim of this study is to investigate awareness of general public in Montenegro regarding clinical trials. Methods: The data from questionnaire completed by 400 randomly selected people aged 18 and over was collected. The questionnaires included questions about CT awareness and perceptions of CT in addition to demographic information. Results: There were statistically significant gender differences with regards to clinical trials awareness. Only 44,2% of all male subjects versus 70,8% of all female ones were informed about the definition of clinical trials (p<0,001). While 49,8% women thought that medicines on the market were clinically tested, 47,5% men were not sure about that (p=0,037). The main motive for clinical trial enrolment for subjects under the age of 25 and over the age of 50 was curing the existing disease, while for subjects aged 26-50 was eventual financial reimbursement (37,6% and 44,2% versus 34,9%; p<0,001). Conclusions: These results indicate that additional educational efforts are needed in order to improve the awareness of significance of clinical trials. Therefore, the Agency for Medicines and Medical Devices of Montenegro will continue its activities in order to promote clinical trials to the general and professional public.